2003
DOI: 10.3928/0148-4834-20030401-10
|View full text |Cite
|
Sign up to set email alerts
|

Mentoring Youth: A Service-Learning Course Within a College of Nursing

Abstract: Faculty at the University of Southern Maine College of Nursing and Health Care Professions developed a servicelearning course that connected students and faculty with at-risk children in a local community. Nursing students, with faculty supervision and support, developed, implemented, and evaluated interventions to reduce risk factors and increase protective factors to build and strengthen the participants' resiliency. Students enrolled in the service-learning course worked in the community where the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…Our findings also report diverse interventions with mixed outcomes on helping others and youth mental health. Educational, psychosocial, mindfulness and act of kindness interventions had an overwhelmingly positive impact on youths: for example, life satisfaction [33,114,197], experience of positive emotions [200] and improved learning [110,199]. However, there were a few interventionssuch as school-based programs for resilience, and trauma-focused intervention-that showed no change, or even showed a reduction in prosocial behavior [204].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings also report diverse interventions with mixed outcomes on helping others and youth mental health. Educational, psychosocial, mindfulness and act of kindness interventions had an overwhelmingly positive impact on youths: for example, life satisfaction [33,114,197], experience of positive emotions [200] and improved learning [110,199]. However, there were a few interventionssuch as school-based programs for resilience, and trauma-focused intervention-that showed no change, or even showed a reduction in prosocial behavior [204].…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, engaging in prosocial behavior resulted in several positive impacts. The identified studies suggested that youths who engaged in prosocial behavior benefited from increased use of reappraisal [97], coping mechanisms [98], depression-prevention strategies [97][98][99], positive reappraisal [100], higher levels of intentional self-regulation [101], higher levels of strengths and lower levels of distress [102], higher levels of trust [103], passions, relational opportunities, sense of empowerment [104], increased awareness [105], happiness [21,60], positive self-identity [81,106], improved wellbeing [107,108], better morale [109] and positive and safe experiences [110,111]. Some other prosocial strategies involved youths encouraging self-help, and respecting the right of their peers not to seek help [112].…”
Section: Major Themes 331 Relationship Between Helping Others and Men...mentioning
confidence: 99%
See 1 more Smart Citation
“…One example of this is the dearth of research that exists on the impact of GSL programs on host communities (Beaman et al, 2018). In contrast, a significant body of research exists on the benefits of GSL to U.S. college students, including deepening "individuals' cultural understanding and encourag[ing] cultural humility" (Early & Lasker, 2017) and gaining leadership development skills (Childs et al, 2003). Institutions of higher education and program directors may have structured partnerships in a way that is cooperative rather than reciprocal (Worrall, 2007).…”
Section: Fair Trade Learningmentioning
confidence: 99%